Factors Influencing Auditors' Going Concern Opinion - Putri , Rumanintya; Wahyono, Eko; Lambut , Adventinus Kristanto; Hadi, Agus Hari (Accounting Department,, 2022)
Purpose — This research aims to analyze the effect of profitability, liquidity, and firm size on audit opinion concerning manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. Design/methodology/approach—The research methodology used is a quantitative method using panel data, which is a combination of cross-section and time series. The data source used is secondary data obtained from the Indonesia Stock Exchange website. A total of 35 samples of companies were obtained by probability sampling, especially purposive sampling. The data analysis technique used is logistic regression analysis. Findings — The results of this study indicate that profitability has a negative effect and is a sign of the Going Concern Audit Opinion. Liquidity has a negative impact and is significant on the ongoing concern Audit Opinion. In contrast, the company's size has a negative effect but no sign on the Going Concern Audit Opinion. Meanwhile, the variables of Profitability, Liquidity, and Company Size are significantly related to the dependent variable, namely Going Concern Audit Opinion. Practical implications—Companies and management must examine and analyze the factors that can affect the provision of Going Concern Audit Opinions because the company's survival is very important going forward. Originality/value—This paper presents data from the Indonesia Stock Exchange for 35 sample companies. This research is expected to provide empirical findings on the factors influencing auditors’ going concern opinions, which are affected by profitability, liquidity, and firm size. Keywords — Auditing opinion; going concerned; firm size; liquidity; and profitability. Paper type — Analytical Research Paper.